Existence of solutions to the nonhomogeneous steady Magnetohydrodynamic equations. Issue 9 (4th July 2018) - Ma, Xixia
Abstract: We study the nonhomogeneous boundary value problem for the steady Magnetohydrodynamic equations in a two-dimensional bounded domain with multiply connected boundary. We prove that this problem has an admissible solution in an admissible domain if the boundary value is admissible. The proof of the main result uses some property for a weak solution to the transport equations in an admissible domain.